The role of job demands, resources, work-life balance, and supervisor relationships in burnout among Indonesian cardiology residents - Lana Emilia Gondowahjudi; Noermijati Noermijati; Ananda Sabil Hussein; Kusuma Ratnawati (Universitas Brawijaya, 2025)
Background: Several studies have been conducted on the effects of job demands, job resources, work-life balance, and supervisor-resident relationships on burnout syndrome in cardiology residents globally, but no such study has been conducted in Indonesia. Objectives: To investigate the impact of job demands, job resources, work-life balance, and supervisor-resident relationship quality on burnout syndrome among cardiology residents in Indonesia. Methods: A cross-sectional study was conducted among 42 cardiology residents from 10 Indonesian universities from March to July 2024, with data collected online using a validated questionnaire. Results: Our results indicated that there was no significant difference between the burnout and non-burnout groups regarding job demand variables such as emotional demand, mental demand, and work overload (p > 0.05). Similarly, job resources, including work independence, supervisor support, colleague support, schedule flexibility, and feedback, were not significantly associated with the risk of burnout (p > 0.05). Additionally, work-life balance factors such as work time, family time, break time, and supervisor-resident relationships showed no significant association with burnout among residents. Conclusion: The study indicates that job demands, resources, work-life balance, and supervisor-resident relationship quality do not significantly impact burnout in cardiology residents. Other factors may contribute to burnout, and further research is needed to identify these factors to improve prevention efforts.